Collaboration model in e-learning for universities based on agents - Bernuy, Augusto E. (2006)
The paper presents the basic requirements that must cover distance education processes (“e-learning”) in universities. We show the concepts of instruction design, an adaptive learning model for evaluating necessities, accreditation, and quality proposal. The experience indicates that to obtain good results we should evaluate the differences between the criteria of the professor and the criteria of the student about: the educative aspects, the user reaction (in each perspective), the reading aspects (in the student) and complementary material. Thus, collaboration and quality are managed when the learning process is based on design, the designer, the professor, participation level, student profile and his characteristics, the motivations and evaluations. We will need continuous reflection and evaluation for the organizations and the structured learning programs, having looked for educative yield and productive development. The paper is our contribution to work with ethical issues and human collaboration for the information society